Integrated Work Mapping to Optimize Small-Scale Tofu Production : Evidence from Padang, West Sumatra - Khairun Nadiyah; Maria Isfus Senjawati; Muhammad Syarif Hidayat; Kushisa Atta Jaeba (Jurnal IPTEK Bagi Masyarakat, 2026)
This study aims to identify inefficiencies in the tofu production process in small-scale tofu industries in Padang City, West Sumatra, and to propose improvements through an integrated work mapping approach. The analysis employs five types of work mapping tools, namely the operation process chart, flow process chart, layout flow diagram, man–machine chart, and right-hand–left-hand chart. The research method used is a qualitative case study conducted through direct observation, production cycle time measurements, and semi-structured interviews with the owner and workers. The results show that the total production cycle requires approximately 390 minutes, with the soaking stage (120 minutes) and molding stage (60 minutes) being the most time-consuming processes. The flow process chart identifies seven transportation activities with a total time of 16 minutes. Meanwhile, the man–machine chart reveals an imbalance in resource utilization, where the grinding machine operates for 33.1 minutes while the operator is active for only 3.1 minutes, resulting in 30 minutes of idle time. The right-hand–left-hand chart also indicates the dominance of right-hand movements in the cutting process, suggesting ergonomic inefficiency. The novelty of this study lies in the integration of five work mapping tools within a single analytical framework to provide a comprehensive evaluation of process flow, spatial layout, human–machine interaction, and manual motion patterns. The proposed improvements include workflow optimization, task redistribution, ergonomic workstation redesign, and the development of standard operating procedures (SOPs) to enhance efficiency and productivity in small-scale tofu industries.